THE USE OF PARTICIPATION POINT SYSTEM IN TEACHING ENGLISH SPEAKING IN VII GRADE OF SMP BALAI PENDIDIKAN PENGAJARAN BANDUNG - Rizky Fitria Ridyani, - (2009)
ABSTRACT Participation Point System is a system that appreciates students' participation in class by giving them points every time they participate in class. The point is tangible so students can see how far they progress. This study, entitled The Use of Participation Point System in Teaching English Speaking in VIIth Grade of SMP Balai Pendidikan Pengajaran Islam (BPPI) Bandung is aimed to investigate (1) the implementation of Participation Point System (PPS) in a class of SMP BPPI Bandung VIIth grade; (2) problems faced by the teacher who uses PPS (3) students respond toward PPS. This research is conducted using a qualitative approach. It involved a teacher and 31 students of SMP BPPI as the participants. The data were gained from non-participant observation, interviews and questionnaires. The study revealed that the class using PPS was very dynamic; most students were involved in the class activity and paid attention more to the teacher. Most of them appreciated PPS as good method in increasing their confidence to speak in class and their problem toward PPS related with their problem toward English material. On the other hand, teacher's problem toward implementation of PPS appeared in dealing with crowded students, preparing appropriate material, and giving point to students.